Implementation of the City Statute on June 11, 1892: based on the materials of the ordinary South Russian city of Nakhchivan-na-Donu - Levon V. Batiev (RUDN Journal of Law)
Nakhichevan-on-Don was founded in 1779 as the center of an Armenian colony with granted internal autonomy. By the second half of the 19th century, it had developed into a country town predominantly populated by Armenian population. Studying the reform of self-government in the Russian provinces, particularly in cities with distinct historical, socio-economic, and ethno-cultural characteristics, is essential for forming a coherent understanding of urban governance in Russia. Using archival documents and local publications not previously introduced into scientific discourse, this study employs concrete-historical methods to reconstruct the process of organizing and conducting elections for the city duma and administration. It analyzes changes in the number of voters, the composition of the city duma and the administration, and the distribution of responsibilities among its members. The findings reveal that elections were conducted under close supervision by regional authorities. The number of voters in Nakhchivan decreased 2.8 times compared to the previous period, which was still twice the average figure for Russia. Nakhchivan voters demonstrated greater activity compared to neighboring cities, with merchants comprising an overwhelming 82.5% of the electorate. The burghers secured 10 seats while four noblemen were among the deputies. Compared to previous compositions, only five new names appeared in the duma. Of the deputies, only five owned real estate valued between 300 to 1,000 rubles, while 23 deputies had properties valued between 1,000 and 3,000 rubles. Despite the increasing Orthodox population, all mayors and members of the administration were of Armenian-Gregorian faith. The introduction of the City Regulations of 1892 did not lead to significant changes in urban governance in Nakhchivan-on-Don. Further research is required to explore the activities of city government bodies and their relationship with crown authority.